Analisis Pengaruh Gaya Kepemimpinan Transformasional terhadap Komitmen Organisasi dan Organizational Citizenship Behavior (OCB) pada Perawat di Rumah Sakit X - Luthfiana Nur; Rohilatul Jannah; Soliha Soliha (Jurnal Sains dan Kesehatan, 2026)
Having employees with OCB attitudes will have a positive impact on the ease of achieving organizational goals. OCB is the attitude of employees doing many things outside of their duties voluntarily. In contrast, OCB will influence each other with organizational commitment. Organizational commitment is a person's sense of comfort in being part of the organization. The growth of these two things is influenced by the leadership style, in this case, the transformational leadership style. Based on the preliminary survey results, it has been shown that OCB attitudes and organizational commitment are both influenced by leadership style. So, the researcher wants to see the effect of the three. This study uses multiple linear regression research with quantitative research and a questionnaire with a Likert scale. After the analysis had been conducted, the results were H1: Transformational Leadership had a significant effect on Organizational Citizenship Behavior (OCB) in X Hospital nurses, H2: Transformational Leadership has a substantial impact on organizational commitment in X Hospital nurses, and H3: Organizational Commitment had a significant effect on Organizational Citizenship Behavior (OCB) on nurses at Hospital X.